View factors of cylindrical spiral surfaces. (March 2016) - Lebedev, Vladimir A.; Solovjov, Vladimir P.
Abstract: Analytical expressions are presented for the view factors (radiative configuration factors) associated with the flat right cylindrical spiral surface. Such cylindrical spiral systems are widely applied as electrical resistance heating elements for lighting devices, electronic radio tubes, high-speed gas flow heaters, and other appliances used for scientific, industrial and domestic purposes. Derivation of the view factors is based on the invariant principles and the results presented in Lebedev (2000, 2003, 1988)[1–3] . Highlights: Analytical expressions are presented for the view factors associated with the cylindrical spiral surface. The limiting case of the configuration factors for infinitely long spiral.